Etiquette hotline table manners - Schrank, Louise Welsh; Learning Seed Company; Stage Fright Productions (Chicago, Ill. : Learning Seed, 2004)
Eavesdrop on a fictional hotline as distressed callers query the experts on proper table manners. Covers eating in a restaurant and as a guest in someone's home and explains how a table is set and how to use each piece of tableware
Title from title screen
Hostess: Christine Schrank
DVD Format
With English subtitle
Keywords: Table etiquette; Etiquette